IMPLEMENTASI PROGRAM PANCA JANGKA DI YAYASAN DARUNNAJAH MUKOMUKO BENGKULU - Putri Kartiwi, Asti; Miswadi (Manajer Pendididikan, 2024)
This study explores the implementation of the Panca Jangka Program at Yayasan Darunnajah, aimed at enhancing educational quality and character development among students. The program encompasses five main aspects: academics, religious education, social skills, independence, and health. Utilizing qualitative methods, data was collected through interviews and observations. The findings indicate that the Panca Jangka Program successfully creates a positive learning environment and encourages active student participation. This research is expected to serve as a model for other educational institutions in improving student development programs.